Toxic effect of alpha cypermethrin, an environmental pollutant, on myocardial tissue in male wistar rats - Ghazouani, Lakhdar; Feriani, Anouar; Mufti, Afoua; Tir, Meriam; Baaziz, Intissar; Mansour, Hedi Ben; Mnafgui, Kais (Environmental science and pollution research international, 2020)
α-Cypermethrin (CYP) is a pyrethroid insecticide-like environmental pollutant, widely found in the environment. New research links exposure to high levels of CYP to health damage; however, little is known about the effect of CYP on cardiovascular disease. The purpose of the present study was to evaluate, for the first time, biochemical and cardiovascular changes in male rats resulting from subchronic CYP exposure. The animals were divided into three groups: group 1 served as the control, group 2 (CYP1) received 4 mg/kg of CYP by gavage, and group 3 (CYP2) received 8 mg/kg of CYP by gavage, for 8 weeks each. Results showed that both CYP1 and CYP2 markedly increased plasma concentrations of cardiac markers (LDH, CK-MB, and troponin-T). Moreover, compared to the control group, CYP treatment elevated cardiac oxidative stress, as shown by increased MDA level and decreased activity of SOD, CAT, and GSH-Px. In addition, CYP2 caused a significant increase of 42% the concentration of total cholesterol and more than 75% in triglycerides compared to the control group. Furthermore, DNA fragmentation and collagen deposition were both amplified owing to CYP toxicity. This harmful effect was confirmed by a histological study using H-E and Sirius Red staining. Overall, our results clearly proved the cardiotoxicity caused by α-cypermethrin.